Homeopathic Prevention and Management of Epidemic Diseases - Jacobs, Jennifer (Homeopathy, 2018)
Background Homeopathy has been used to treat epidemic diseases since the time of Hahnemann, who used Belladonna to treat scarlet fever. Since then, several approaches using homeopathy for epidemic diseases have been proposed, including individualization, combination remedies, genus epidemicus, and isopathy.Methods The homeopathic research literature was searched to find examples of each of these approaches and to evaluate which were effective.Results There is good experimental evidence for each of these approaches. While individualization is the gold standard, it is impractical to use on a widespread basis. Combination remedies can be effective but must be based on the symptoms of a given epidemic in a specific location. Treatment with genus epidemicus can also be successful if based on data from many practitioners. Finally, isopathy shows promise and might be more readily accepted by mainstream medicine due to its similarity to vaccination.Conclusion Several different homeopathic methods can be used to treat epidemic diseases. The challenge for the future is to refine these approaches and to build on the knowledge base with additional rigorous trials. If and when conventional medicine runs out of options for treating epidemic diseases, homeopathy could be seen as an attractive alternative, but only if there is viable experimental evidence of its success.
Keywords: homeopathy; epidemic diseases; homeoprophylaxis; nosodes; isopathy; genus epidemicus